2017
DOI: 10.3233/jad-160882
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress in Alzheimer’s Disease Research, Part 1: Pathology

Abstract: The field of Alzheimer's disease (AD) research has grown exponentially over the past few decades, especially since the isolation and identification of amyloid-β from postmortem examination of the brains of AD patients. Recently, the Journal of Alzheimer's Disease (JAD) put forth approximately 300 research reports which were deemed to be the most influential research reports in the field of AD since 2010. JAD readers were asked to vote on these most influential reports. In this 3-part review, we review the resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
62
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(63 citation statements)
references
References 265 publications
(351 reference statements)
0
62
0
1
Order By: Relevance
“…Extracellular Aβ plaques and intracellular neurofibrillary tangles (NFTs) composed of hyperphosphorylated tau proteins in the cerebral cortex and hippocampus are the typical pathological changes of AD [2,7]. It is well recognized that the severity of dementia is strongly correlated with NFTs rather than senile plaques [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Extracellular Aβ plaques and intracellular neurofibrillary tangles (NFTs) composed of hyperphosphorylated tau proteins in the cerebral cortex and hippocampus are the typical pathological changes of AD [2,7]. It is well recognized that the severity of dementia is strongly correlated with NFTs rather than senile plaques [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…There are two typical pathological hallmarks in AD: the accumulation of amyloid plaques consisting of amyloid-β (Aβ) proteins in the brain parenchyma of AD patients and the formation of neurofibrillary tangles composed of hyperphosphorylated tau filaments [6]. Additional pathological changes in AD include the presence of chronic neuroinflammation, gradual neuronal loss and synaptic dysfunction, and impairments in the blood-brain barrier (BBB) [7]. Age is the biggest nongenetic risk factor for AD, as revealed by the exponential increase in the incidence of AD with the advancement of age [2].…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that AD is a chronic and progressive neurodegenerative disease, with gradual memory loss as the main clinical syndrome. In the general pathology, there is nervous tissue atrophy, neuron and synapse loss, as well as neuronal subcellular structure and function disorders, which are all involved in the development and clinical manifestation of AD 1 2 . It is reported that when animals were intracerebroventricularly injected with Aβ, some neurotoxic events occur in the brain involving neuron loss, calcium homeostasis disruption, neuron apoptosis, and reactive oxygen species overproduction 3 .…”
Section: Introductionmentioning
confidence: 99%